2021
DOI: 10.3390/cancers14010047
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Marker Associated with CTC in Colorectal Cancer in Mononuclear Cells of Patients with Benign Inflammatory Intestinal Diseases

Abstract: Colorectal carcinoma (CRC) belongs to the most common tumor entities in western countries. Circulating tumor cells (CTC) in blood of CRC patients are a powerful prognostic and predictive biomarker. However, whether CTC-associated markers can also be used for early CRC detection and discrimination from benign diseases is not known. This study investigated the presence of CTC-associated markers CK20, PLS3, LAD1, and DEFA5 in blood of patients with benign inflammatory intestinal disease (IID) and their correlatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 40 publications
3
5
1
Order By: Relevance
“…To further validate this marker for detection of CTC and DTC in EC patients and with this as an indicator of malignancy, CK20 expression was also assessed in the blood and bone marrow of a control cohort (comprising healthy blood donors and bone marrow donors with non-malignant diseases) showing a positive detection of CK20 in the blood (63%) and bone marrow (42%). Our findings are in line with studies that have also demonstrated CK20 positivity in the blood of healthy donors [ 32 ]. Importantly, it has to be taken into account that all RT-PCR analyses were performed in triplicate with the samples from the EC patients being more often triple or at least double positive for CK20 (but also for DEFA5) than the control cohort.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…To further validate this marker for detection of CTC and DTC in EC patients and with this as an indicator of malignancy, CK20 expression was also assessed in the blood and bone marrow of a control cohort (comprising healthy blood donors and bone marrow donors with non-malignant diseases) showing a positive detection of CK20 in the blood (63%) and bone marrow (42%). Our findings are in line with studies that have also demonstrated CK20 positivity in the blood of healthy donors [ 32 ]. Importantly, it has to be taken into account that all RT-PCR analyses were performed in triplicate with the samples from the EC patients being more often triple or at least double positive for CK20 (but also for DEFA5) than the control cohort.…”
Section: Discussionsupporting
confidence: 93%
“…In the control group, 57.8% of the blood and 91.6% of the bone marrow samples were positive for DEFA5, which declined to 13% and 45%, respectively, after cut-off calculation. The higher detection rates of DEFA5 in the blood of EC patients compared to healthy controls correspond to the findings for CRC patients published by Born et al, and the findings by Lisitsyn et al, albeit the latter study comprises only a little number of patients and control donors [28,32].…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations